2020
DOI: 10.7570/jomes20040
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 6 Months of Dapagliflozin Treatment on Metabolic Profile and Endothelial Cell Dysfunction for Obese Type 2 Diabetes Mellitus Patients without Atherosclerotic Cardiovascular Disease

Abstract: Background: Sodium-glucose cotransporter 2 inhibitors reduce the risk of cardiovascular death in individuals with type 2 diabetes mellitus (T2DM) and cardiovascular disease, but the effect of these inhibitors on early cardiovascular disease remains unknown. This study evaluated the effect of dapagliflozin on the metabolic profiles and endothelial cell function in obese patients with T2DM without established cardiovascular disease. Methods: We enrolled 140 patients with a mean age, weight, and body mass index (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 28 publications
1
8
0
1
Order By: Relevance
“…A recent prospective study reported a decrease in the arterial stiffness in 32 patients treated with dapaglizofin for 12 months [ 93 ]. Similar results have been reported by Hong et al, in 140 diabetic patients treated with dapaglizofin for 6 months [ 94 ]. Interestingly, the use of gliflozins is associated with a 11% reduction in vascular stiffness, which was independent from the use of glitazones [ 95 ].…”
Section: Pharmacological Treatment Of Arterial Stiffnesssupporting
confidence: 90%
“…A recent prospective study reported a decrease in the arterial stiffness in 32 patients treated with dapaglizofin for 12 months [ 93 ]. Similar results have been reported by Hong et al, in 140 diabetic patients treated with dapaglizofin for 6 months [ 94 ]. Interestingly, the use of gliflozins is associated with a 11% reduction in vascular stiffness, which was independent from the use of glitazones [ 95 ].…”
Section: Pharmacological Treatment Of Arterial Stiffnesssupporting
confidence: 90%
“…However, the study measured body composition by bioelectrical impedance analysis, which estimates body composition with lower accuracy than DXA used in our study and the study conducted by Sasaki et al 30 Similar to our results, a recent real‐world analysis (n = 140) among obese patients with T2D from Korea, reported significant decrease in total body weight (from 83.01 ± 16.42 to 79.70 ± 16.13 kg), BMI (from 30.3 ± 4.7 to 29.1 ± 4.7 kg/m 2 ), BF mass (from 31.09 ± 9.90 to 28.31 ± 9.91 kg) and BF% (from 36.75% ± 7.56% to 35.12% ± 7.19%; p < .001) with dapagliflozin monotherapy for 6 months. These results indicate that Korean patients with T2D prescribed with dapagliflozin may have weight reduction, predominantly driven by BF mass loss 32 …”
Section: Discussionmentioning
confidence: 75%
“…In the EDIFIED study involving high-risk diabetic patients due to underlying CHD, a 12-week therapy with dapagliflozin in addition to insulin and metformin failed to demonstrate a significant improvement of FMD, despite a worsening trend of this parameter within the placebo group [123]. A later study of T2DM patients with no history of CVD demonstrated that a six-month dapagliflozin therapy resulted in a significant improvement of central PWV, probably caused by the reduction of body fat, especially visceral fat, rather than an amelioration of vascular function [124,125].…”
Section: Results From Clinical Studiesmentioning
confidence: 99%